Doubly‐Charged Xe Ions Evidenced by Time Resolved RPA Measurement in the Far Field Plume of a Low‐Power HET. Issue 7 (8th June 2015) - Gibert, T.; Balika, L.; Diop, F.; Bouchoule, A.
Abstract A low power Hall Effect Thruster (HET), based on a permanent magnet circuit, was investigated in the GREMI laboratory facility. The thruster operated in the working range between 50 and 300 W and the previously measured thrust is between 4 and 16 mN for an anodic efficiency respectively between 15% and 27%. The pulsed character of the thruster current is an important feature of this HET. The ion current's bursts are recorded at 30 and 70 cm from the exit plane in the thruster plume and are time‐resolved, which lead to a preliminary analysis of the time of flight (TOF) phenomena. This paper presents a detailed study of these bursts of ion current in the plume. The total ion current is shown to be a superposition of 2 distinct contributions of charged species. In complement, a controlled single current interruption in stable anodic current condition leads to exactly the same features than in oscillating mode. This crucial verification garantees the validity of the time of flight origine of the two distinct contributions. Then, the slower one is the more intense and is proportional to the ion Xe+ current whereas the faster one could be attributed either to doubly‐charged Xe++ or to superfast Xe+. The work presents a way to determine unambiguously the nature of the fast contribution by recording the Retardated Potential Analyser (RPA) signals at various repelling grid potentials with respect to time. The energy distribution of the 2 wellseparated contributions are reconstructed and confirms the contribution of doubly‐charged xenon ions (Xe++) in the plume. This way of RPA collecting data and interpretation presents the main advantage tobe an easy way for the identification of the nature of the charged species in the plume. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)